The impact of gender, socioeconomic status and locality on the development of student patterns of alcohol consumption and harm. Issue 4 (13th August 2019) - Evans, Melissa; Lester, Leanne; Midford, Richard; Cahill, Helen Walker; Foxcroft, David; Waghorne, Robyn; Venning, Lynne
Abstract : Purpose: The consequences of problematic alcohol consumption fall heavily on Australian adolescents, with this population at increased risk of death, serious injury and other harm. Research regarding whether gender, socioeconomic status (SES) or locality play a role in young people's alcohol consumption and related harm is limited in Australia. The purpose of this paper is to determine whether Victorian students' patterns of alcohol uptake, consumption and related harm differed between gender, SES and locality. Design/methodology/approach: The study involved secondary analysis of student data from the Drug Education in Victorian Schools harm minimisation drug education programme, undertaken in 21 Victorian government schools over three years The initial cohort of 1, 752 students was followed during Years 8, 9 and 10, when their average age would have, respectively, been 13, 14 and 15 years. Findings: There were no gender differences in drinking uptake, consumption or harm. Students with low SES were more likely to have consumed a full drink of alcohol and also experienced more alcohol-related harm. Students living in a regional/rural area were more likely to have engaged in high alcohol consumption. Originality/value: The findings of this study highlighted that different student demographics have an impact on patterns of alcohol consumption, vulnerability and harm. Students with low SES, living in a regional/rural area, are more at risk than students with higher SES living in a fringe metro/major regional or metro area. Future school harm minimisation drug education programmes should consider the needs of students with demographics that make them more susceptible to higher consumption and harm.